Analisis Pemanfaatan Media Sosial bagi Remaja Muslim : Studi Kasus Penggunaan Instagram dan TikTok - Salsabila Nisrina; Muhammad Fadhilah Al Atsari; Adhi Kusuma (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2025)
Social media has become an inseparable part of adolescents' lives, including as a means of obtaining information and forming religious identity. On the one hand, Instagram and TikTok provide wide access to creative and interesting da'wah content, increase understanding of Islam, form a community of religious courage, and encourage positive expression in the form of Islamic content. However, on the other hand, both also open up great opportunities for adolescents to be exposed to content that is contrary to Islamic values, such as a hedonistic lifestyle, clothing that is not in accordance with Islamic law, and behavior that reduces the quality of worship and real social interaction. In addition, the role of the environment such as family, peers, and religious figures is an important factor in shaping how adolescents use social media. Proper guidance can help adolescents sort content according to Islamic teachings and make social media an effective means of da'wah. On the other hand, without adequate guidance, social media has the potential to become a source of disturbance and deviation of values. Therefore, media literacy and religious awareness are needed so that Muslim adolescents can use Instagram and TikTok wisely and in line with Islamic teachings.